2014
DOI: 10.1017/s031716710001653x
|View full text |Cite
|
Sign up to set email alerts
|

D-Serine in Neurobiology: CNS Neurotransmission and Neuromodulation

Abstract: RÉSUMÉ: La D-sérine en neurobiologie : neurotransmission et neuromodulation dans le SNC. l'homochiralité est fondamentale à la vie. Chez les organismes vivants, seuls les acides aminés lévogyres sont utilisés comme substrats pour la polymérisation et la formation de peptides et de protéines. Cependant, des acides aminés dextrogyres ont été détectés récemment dans différents organismes vivants dont des mammifères. parmi ces acides daminés, la d-sérine a été la plus étudiés. la d-sérine jouerait un rôle importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 202 publications
0
19
0
Order By: Relevance
“…Serine exists in two forms: L-serine and D-serine, and each isomer has similar chemical and physical properties (Bardaweel et al, 2014). While both forms exist in the brain, D-serine distribution is parallel to the distribution of NMDA glutamate receptors (Bardaweel et al, 2014), and D-serine binds three hundred times more strongly than L-serine at the NR1 subunit of NMDAR (Furukawa and Gouaux, 2003).…”
Section: 0 1h-mrs In Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…Serine exists in two forms: L-serine and D-serine, and each isomer has similar chemical and physical properties (Bardaweel et al, 2014). While both forms exist in the brain, D-serine distribution is parallel to the distribution of NMDA glutamate receptors (Bardaweel et al, 2014), and D-serine binds three hundred times more strongly than L-serine at the NR1 subunit of NMDAR (Furukawa and Gouaux, 2003).…”
Section: 0 1h-mrs In Schizophreniamentioning
confidence: 99%
“…Serine exists in two forms: L-serine and D-serine, and each isomer has similar chemical and physical properties (Bardaweel et al, 2014). While both forms exist in the brain, D-serine distribution is parallel to the distribution of NMDA glutamate receptors (Bardaweel et al, 2014), and D-serine binds three hundred times more strongly than L-serine at the NR1 subunit of NMDAR (Furukawa and Gouaux, 2003). Serum D-serine is typically reduced in adults with schizophrenia (Hashimoto et al, 2003; Calcia et al, 2012), and a recent meta-analysis found that serum levels of total serine are elevated in adults with schizophrenia (Brouwer et al, 2013).…”
Section: 0 1h-mrs In Schizophreniamentioning
confidence: 99%
“…Thirty years ago, neuromodulation was considered to be a physiological process of regulation of neuronal activity by neuromodulators or neurotransmitters, 10 such as acetylcholine, norepinephrine, histamine, serotonin, dopamine, and a variety of neuropeptides, glutamate, D-serine, gamma-aminobutyric acid, and glycine. [11][12][13][14][15][16] Drugs targeting neurotransmitters can affect the related neural systems.…”
Section: Neuromodulationmentioning
confidence: 99%
“…It is also known that D-serine inhibits the symptoms of the schizophrenia induced by phencyclidine [11], and that treatment of schizophrenic patients with D-serine, as an add-on agent to other antipsychotics, improves negative, positive and cognitive symptoms [12]. D-serine has been also involved in the neuropathogenesis of HIV-1 associated neurocognitive disorders, epilepsy, Alzheimer's disease, amyotrophic lateral sclerosis, neurotoxicity, ischemia and synaptic plasticity, and it has been reported that the extracellular level of D-serine was regulated by the AMPA glutamate receptor [3,[13][14][15][16][17][18][19]. Moreover, it was found that the level of D-serine decreases with age in the mouse cerebellum [3].…”
Section: Introductionmentioning
confidence: 99%